Job satisfaction among physical education teachers: A systematic literature review - Gazali, Novri; Saad, Norazlinda; Setiawan, Edi; Lobo, Joseph (Edu Sportivo: Indonesian Journal of Physical Education, 2024)
Background Problems: In recent decades, physical education teacher job satisfaction has become a topic of interest in academic literature. The important role of physical education teachers' job satisfaction in the quality of teaching and its potential to influence student achievement have attracted attention. Research Objectives: This study aims to comprehensively analyse the level of job satisfaction among physical education teachers through a systematic review of the existing literature. Methods: We selected articles containing information on this topic from two databases (Scopus and Web of Science). We conducted the search according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. After the exclusion criteria, only 26 articles were categorized, all published between 2014 and 2023. Findings/Results: This research reveals that physical education teachers’ job satisfaction has been investigated in 13 countries, with Turkey, the United States, and Greece being the main focus. Although the majority of physical education teachers expressed high levels of satisfaction, significant differences in satisfaction levels emerged between them. For example, in Slovakia and Poland, satisfaction levels were relatively low. The findings underline that administrative support, work-life balance, and economic considerations are key factors that influence physical education teachers’ job satisfaction. However, in this context, money and rewards, working conditions, and the availability of resources also play an important role in determining teacher satisfaction. Conclusion: The findings from this study highlight the need for a deeper understanding of the diverse factors impacting job satisfaction among physical education instructors. We can develop more effective policies and practices to improve teachers’ well-being and performance at both local and global levels by understanding these nuances. We suggest further investigations into job satisfaction among physical education teachers in the Asian region, particularly focusing on Southeast Asia. Additionally, exploring variables such as leadership, self-efficacy, school climate, and culture in future research can offer deeper insights into the determinants of job satisfaction.